Rencana Bisnis Pengembangan Usaha Katering “Paon Jahe Sereh Catering” - Bayu Purna Yudha (Universitas Tarumanagara, 2021)
The culinary industry in Indonesia continues to grow, supported by many traditional foods and foods from abroad. Based on data compiled from Badan Ekonomi Kreatif, culinary industry contributed 41,4% of the gross domestic product (GDP) of the creative economy subsector in 2016. Until 2018, the total contribution of the creative economy to GDP reached Rp. 1,100 trillion. “Paon Jahe Sereh Catering”. offers hygienically processed food and provides quality services. The purpose of developing the “Paon Jahe Sereh Catering” business is to expand the target market from school catering, as well as employee catering and family catering. From the results of calculations on the financial aspects for 5 years, NPV of 415.155.01, PI of 2.84, IRR of 45,706% are obtained, and payback periode is 2 years 6,2 month, so that from these results it can be concluded that the catering business development project is feasible to run. Industri kuliner di Indonesia terus berkembang, didukung dengan banyaknya makanan tradisional maupun makanan dari luar negeri. Berdasarkan data yang dihimpun dari Badan Ekonomi Kreatif, industri kuliner berkontribusi 41,4% terhadap produk domestik bruto (PDB) subsektor ekonomi kreatif tahun 2016. Hingga 2018, total kontribusi ekonomi kreatif terhadap PDB mencapai Rp. 1.100 triliun. “Paon Jahe Sereh Catering” menawarkan makanan yang diproses secara higienis dan memberikan layanan yang berkualitas. Tujuan dari pengembangan usaha “Paon Jahe Sereh Catering” ini adalah memperluas target pasar dari katering sekolah, juga ke katering karyawan dan katering keluarga. Dilihat dari perhitungan keuangan selama 5 tahun, dengan investasi awal Rp. 225.000.000,- didapatkan NPV sebesar 415.155.017, PI sebesar 2,84, IRR sebesar 45,706% dan Payback Period 2 tahun 6,2 bulan, sehingga dari hasil tersebut maka dapat ditarik kesimpulan bahwa proyek pengembangan usaha katering ini layak untuk dijalankan.